(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Algebra thinking is a staple of thinking and analysis in mathematics. In addition, algebraic thinking can also improve students’ critical thinking skills. However, students’ algebraic thinking skills are still low when compared to developed countries. Whereas in the algebra material the grades of students of SMP Negeri 4 Petarukan based on the national exam were good but not for other material. It is possible that there are errors in using algebra so that differences occur. Then it is necessary to analyze the error in order to get an answer in order to minimize errors. The subjects in this study were 15 grade IX students of SMP Negeri 4 Petarukan, through the written test KBAS obtained 6 students each, one student representing six stages of algebraic thinking skills. Data collection techniques in this study were 2 written tests and interview tests. From the results of research errors that are mostly done in concept errors are not quite right in writing an example, in principle errors are less precise in writing equivalent signs, as well as operating errors in the less systematic way of solving them. For each subject at the algebraic thinking ability stage it is concluded that the types of errors are not the same.